1993
DOI: 10.1128/jvi.67.11.6674-6681.1993
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of rabies and borna disease viruses on immediate-early- and late-response gene expression in brain tissues

Abstract: In situ hybridization and Northern blot analysis were used to examine expression of the immediate-early-response genes (IEGs) egr-1, junB, and c-fos, and the late response gene encoding enkephalin in the brains of rats infected intranasally with Borna disease virus (BDV) or rabies virus. In both Borna disease and rabies virus infections, a dramatic and specific induction of IEGs was detected in particular regions of the hippocampus and the cortex. Increased IEG mRNA expression overlapped with the characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…6B). It has also been reported that there is a good correlation between Egr-1 and viral RNA expressions in the mouse brains infected with Rabies and Borna disease viruses, which raises the possibility that Egr-1 expression may induce some phenotypic changes in neurons that render them more susceptible to viral replication (Fu et al, 1993). The other potential consequence of Egr-1 induction is to promote host cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6B). It has also been reported that there is a good correlation between Egr-1 and viral RNA expressions in the mouse brains infected with Rabies and Borna disease viruses, which raises the possibility that Egr-1 expression may induce some phenotypic changes in neurons that render them more susceptible to viral replication (Fu et al, 1993). The other potential consequence of Egr-1 induction is to promote host cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in addition to MHV as found in this study, it has been shown that Egr-1 gene expression is induced by infections with diverse groups of viruses. For example, Egr-1 expression was induced in the brain tissue in experimental mice infected with Rabies virus and Borna disease virus (BDV), in a number of human cells infected with human foamy virus (HFV), in human T-cell leukemia virus type 1-(HTLV-1) or type 2 (HTLV-2)transformed cell lines, in B-lymphocytes infected with Epstein-Barr virus (EBV), and in Bc-2 cells latently infected with Kaposi's sarcoma-associated herpesvirus (KSHV) (Fu et al, 1993;Wagner et al, 2000;Calogero et al, 1996;Wright et al, 1990;Sukhatme et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Egr-1 is involved in the gene expression and the replication of several viruses such as Epstein Barr virus [31,32], HSV-1 [17,33,34], JC virus [35], orthopox virus [36], murine corona virus [37], rabies virus [38,39], borna disease virus [39], human foamy virus [40], Japanese encephalitis virus [38], HTLV-I [41,42] and HTLV-II [42]. In most cases, Egr-1 was induced after the virus targeted neural cells and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HEP-RANTES and particularly HEP-IP10 not only induced high and persistent expression of the intended chemokines but also induced high expression of other chemokines. High and persistent infiltration of inflammatory cells, particularly neutrophils and T cells, was also observed in the CNS, which can produce neurotoxins, free radicals, and proinflammatory cytokines, causing CNS destruction (13).…”
Section: Discussionmentioning
confidence: 99%